Kesejahteraan hidup: Kajian petani di kawasan penanaman padi di Negeri Perlis - Md Yusof, Azizah; Ali, Jamal; Kamarudin, Roslina (2013)
In line with the objectives of Vision 2020, the government intends to increase the standard of living for low-income communities.One of the branches or joint can be done is increase the well-being of the people.Increased standard of living is one of the agenda listed in the Government Transformation Program and is contained in one of the six National Key Result Areas (NKRA).Rising standards of living or well-being is one thing on the agenda for national development.Many developed countries have made the issue of well-being as one of the agenda in the development of their country and so is Malaysia.In fact this was expressed by former Prime Minister, Tun Mahathir said, despite their well-being is not one of important economic indicators, but many countries have now started paying attention to this matter because of the progress of a nation can only be measured by the quality of life for people who improved continuously.Tan Sri Muhyiddin also said that in Malaysia, the farming community is one of the groups that need to be addressed as though our country identified as a successful economy by the World Bank but, there are still groups of people who are not farmers in particular pleasures and their development seems to be on the outskirts of the country's development process (Mohd Shaladdin et al, 2006).If the matter is not resolved, then it would certainly disrupt the achievement of goals and subsequent well -being of society as a whole.This condition will prevent or at least delay the attainment of Vision 2020.Many agriculture-related policies have been implemented, but its effect is observed particularly difficult aspect of well-being.Thus, the study of the well-being of farmers should be conducted to ensure its well-being in line with the goal of development policies carried out over the years. This study tried to peel the well-being position’s of the farmers in rice growing areas around the state of Perlis and try to identify the factors that influence their level of well-being.Based on sustainable livelihood approach, all data and information gathered was analyzed using a factor analysis and structural equation modeling.The study found that the welfare of rice farmers living in the MADA area Perlis is influenced by their satisfaction on four things: housing, income, expenses and the ownership of the assets as a whole.